Diagram Kendali Adaptive Exponentially Weighted Moving Average Bayesian dalam Pengendalian Penyaluran Air Minum - Muhammad Farhan Praja Utama; Teti Sofia Yanti (Jurnal Riset Statistika, 2024)
Abstract. Process control is one of the statistical methods in maintaining product quality. One of the process control methods used in statistical quality control is a control diagram, which is a diagram used to describe the condition of an observation in a certain period of time, whose observation value is limited by the upper control limit (BKA) and lower control limit (BKB) to control the observation. Drinking water is one of the main needs needed by the community. In an effort to fulfill the community's need for drinking water availability, appropriate steps are needed in an effort to control the drinking water distribution process at drinking water companies so that the distribution process becomes more effective. This research was conducted to see the drinking water distribution process at PT.X as a step to control the distribution process. Researchers use the Adaptive Exponentially Weighted Moving Average (AEWMA) control chart by utilizing the Bayesian theorem so that the threshold value of the Bayes confidence interval derived from the posterior distribution is obtained. The results obtained that the AEWMA control chart is quite effective in providing an overview of the movement of the process by showing values that are in control and values that are out of control. Abstrak. Pengendalian proses merupakan salah satu metode statistik dalam menjaga kualitas produk. Salah satu metode pengendalian proses yang digunakan dalam pengendalian kualitas statistik adalah diagram kendali, yaitu diagram yang digunakan untuk menggambarkan kondisi suatu pengamatan dalam periode waktu tertentu, yang nilai pengamatannya dibatasi oleh batas kendali atas (BKA) dan batas kendali bawah (BKB) untuk mengendalikan pengamatan. Air minum merupakan salah satu kebutuhan utama yang dibutuhkan oleh masyarakat. Dalam upaya pemenuhan kebutuhan masyarakat akan ketersediaan air minum diperlukan langkah yang tepat dalam upaya pengendalian proses penyaluran air minum pada perusahaan air minum agar proses penyaluran menjadi lebih efektif. Penelitian ini dilakukan untuk melihat proses penyaluran air minum di PT.X sebagai langkah pengendalian proses penyalurannya tersebut. Peneliti menggunakan diagram kendali Adaptive Exponentially Weighted Moving Average (AEWMA) dengan memanfaatkan teorema bayesian sehingga diperoleh nilai threshold dari interval kepercayaan bayes yang berasal dari distribusi posterior. Adapun hasil yang diperoleh bahwa diagram kendali AEWMA cukup efektif dalam memberikan gambaran pergerakan proses dengan menunjukan nilai-nilai yang berada dalam kendali dan nilai yang out of control.